2023
DOI: 10.3390/antiox12061289
|View full text |Cite
|
Sign up to set email alerts
|

Brain Iron Metabolism, Redox Balance and Neurological Diseases

Abstract: The incidence of neurological diseases, such as Parkinson’s disease, Alzheimer’s disease and stroke, is increasing. An increasing number of studies have correlated these diseases with brain iron overload and the resulting oxidative damage. Brain iron deficiency has also been closely linked to neurodevelopment. These neurological disorders seriously affect the physical and mental health of patients and bring heavy economic burdens to families and society. Therefore, it is important to maintain brain iron homeos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 313 publications
0
14
0
Order By: Relevance
“… 16 Some studies have confirmed that the deposition of brain iron may promote oxidative stress, leading to damage of nerve cells, which in turn affects neural transmission and exacerbates the development of cognitive impairment. 41 In addition, many scholars have conducted research on copper homeostasis imbalance related to cognitive disorders. The study found that the increased copper level in the hippocampus may be one of the pathogenesis of cognitive dysfunction in AD and type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“… 16 Some studies have confirmed that the deposition of brain iron may promote oxidative stress, leading to damage of nerve cells, which in turn affects neural transmission and exacerbates the development of cognitive impairment. 41 In addition, many scholars have conducted research on copper homeostasis imbalance related to cognitive disorders. The study found that the increased copper level in the hippocampus may be one of the pathogenesis of cognitive dysfunction in AD and type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Abnormal levels of Fe 3 + in the body can lead to a variety of diseases: excess Fe 3 + can cause diabetes, heart failure, liver damage and Alzheimer's disease, while Fe 3 + deficiency can lead to iron deficiency anaemia, reduced immunity and neurological disorders. [5][6][7][8][9][10][11] Therefore, the detection of Fe 3 + ions is of great importance. Traditional methods for the detection of Fe 3 + ions are atomic absorption spectrometry, inductively coupled plasma mass spectrometry and UV-vis spectrophotometry etc.…”
Section: Introductionmentioning
confidence: 99%
“…Trivalent iron (Fe 3+ ) is an important trace metal ion and plays key roles in many physiological and pathological processes [1–4] . Abnormal levels of Fe 3+ in the body can lead to a variety of diseases: excess Fe 3+ can cause diabetes, heart failure, liver damage and Alzheimer's disease, while Fe 3+ deficiency can lead to iron deficiency anaemia, reduced immunity and neurological disorders [5–11] . Therefore, the detection of Fe 3+ ions is of great importance.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the maintenance of cellular iron homeostasis must be tightly regulated by a multitude of iron uptake (TfR and DMT1), iron storage (ferritin), iron export (ferroportin 1; FPN1), and its ligand, the master iron-regulatory hormone hepcidin. These mechanisms concomitantly occur to ensure the normal physiological levels of cytosolic LIP for the cellular requirements and permit the safe handling of iron in the brain [ 6 8 ]. Recent studies have demonstrated that the increase in the NTBI pool is coupled with the neuroinflammation response to proinflammatory cytokines release and is considered to increase brain aging and several neurodegenerative diseases [ 9 ].…”
Section: Introductionmentioning
confidence: 99%